Relationship Maintenance pada Pasangan yang Menikah Dini - Yuanita Avisha Putri; Netty Dyah Kurniasari (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to find out relationship maintenance in couples who get married at an early age. This study uses a qualitative descriptive approach, using the Relationship Maintenante theory which discusses 6 aspects, namely, positivity, openness, certainty, social networking, and task sharing. Relationship maintenance is used to keep the relationship harmonious, happy, and lasting throughout the relationship. It was found that the decision to get married at a young age was caused by various factors, including arranged marriage from parents, economic conditions, education, and desires from oneself. The results of the study show that good communication, openness, and honesty are the keys to maintaining a harmonious relationship. Couples who marry at an early age also show a positive attitude and support each other in facing challenges, and rely on physical touch to relieve tension. In addition, support from social networks plays an important role, although couples tend to choose to solve problems independently. The division of duties in the household occurs naturally, based on the abilities of each couple. These findings emphasize the importance of effective communication and emotional support in building strong and harmonious relationships among couples who marry at a young age.